(untitled) (Revista Contexto & Saúde, 2026)
Objective: Validate the Other as Shamer (OAS) scale in Brazilian adolescents. Methods: The cross-culturally adapted version for Brazil (B-OAS) was administered to 325 adolescents aged 12 to 18 from Northeast Brazil. Psychometric properties analyzed were internal consistency, temporal stability (intraclass correlation coefficient – ICC), convergent validity (Depression, Anxiety and Stress Scale - DASS-21), discriminant validity (sociodemographic variables), predictive validity (dental caries and occlusal aspects) and factorial validity (exploratory factor analysis – EFA and confirmatory factor analysis -CFA) (α = 5%). Results: The instrument exhibited excellent internal consistency (α = 0.91; ω = 0.91) and stability (ICC = 0.96). A significant positive correlation was found between B-OAS and DASS-21 scores (rs = 0.66). EFA suggested a single-factor solution (41.6% variance). No associations were found between B-OAS scores and the presence of dental caries or the need for orthodontic treatment (p = 0.55). Scores were significantly higher in female adolescents (p = 0.003) and those with a family income of up to the monthly minimum wage (p = 0.025). Conclusion: B-OAS had satisfactory psychometric properties for Brazilian adolescents and, despite not being associated with the oral problems analyzed, it can be reliably used for other situations related to external shame.